Insights from DNA Barcodes-Based Phylogenetic Analysis of Medicinal Plants and Estimation of Their Conservation Status: A Case Study in the Tianshan Wild Forest, China - Aerguli Jiamahate; Tohir A. Bozorov; Jiancheng Wang; Jianwei Zhang; Hongxiang Zhang; Xiyong Wang; Honglan Yang; Daoyuan Zhang (Plants)
The Tianshan wild fruit forest region is a vital repository of plant biodiversity, particularly rich in the unique genetic resources of endemic medicinal plants in this ecological niche. However, human activities such as unregulated mining and excessive grazing have led to a significant reduction in the diversity of these medicinal plants. This study represents the first application of DNA barcoding to 101 medicinal plants found in the Tianshan wild fruit forests, using three genetic loci along with morphological identification methods. A phylogenetic analysis was performed to delineate species relationships. The results indicate that the internal transcribed spacer (ITS) region has been identified as the most reliable barcode for species identification across different families, while combining data from multiple gene segments can improve species detection. Moreover, the Analytical Hierarchy Process (AHP) was employed to assess and prioritize the 101 medicinal plants, highlighting 23 species as candidates for urgent conservation efforts in the region. The approaches and insights from this study provide a significant benchmark for DNA barcoding studies on medicinal plants with local significance and establish an evaluative framework for the conservation of biodiversity and the surveillance of genetic resources among medicinal plants in the Tianshan wild fruit forest area.